Greenberg's handbook of neurosurgery - Greenberg, Mark S., ....- (New York : Thieme, 2023)
"This 10th edition of the Handbook of Neurosurgery includes newly updated information for the classification of tumors from the 5th edition of the WHO Classification of Tumors series, numerous new figures and tables, and revisions throughout"--
Anatomy and physiology - General and neurology - Imaging and diagnostics - Developmental anomalies - Coma and brain death - Infection - Seizures - Pain - Peripheral nerves - Neurophthalmology and neurotology - Tumors of the nervous and related systems - Other tumors and tumor-like conditions - Head trauma - Spine trauma - Non-traumatic spine and spinal cord conditions - Subarachnoid hemorrhage and aneurysms - Vascular malformations - Stroke and occlusive cerebrovascular disease - Intracerebral hemorrhage - Outcome assessment - Differential diagnosis - Procedures, interventions, operations - Index.
Preceded by Handbook of neurosurgery / Mark S. Greenberg. Ninth edition. [2020].
Includes bibliographical references and index.
Keywords: Nervous system -- Diseases -- Surgery; Nervous system -- Diseases; Nervous system -- Surgery; Nervous System Diseases -- surgery; Neurosurgical Procedures; Nervous System Diseases; Système nerveux -- Maladies; Neurochirurgie; Handbook